2006
DOI: 10.1016/j.jcv.2005.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Detection and pathogenicity of human metapneumovirus respiratory infection in pediatric Italian patients during a winter–spring season

Abstract: (i) Human metapneumovirus is a major viral pathogen in the Italian pediatric patient population; (ii) the severity of lower respiratory tract infections approaches that of human respiratory syncytial virus; (iii) there are preliminary indications that the duration of virus excretion may reach 2-3 weeks and that the level of viral load in NPA correlates with the clinical stage of human metapneumovirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
46
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 37 publications
11
46
0
1
Order By: Relevance
“…[2][3][4][5]8,12,13] According to other reports, [5] our results conÞ rmed that wheezing and cough were in order the most prevalent sign and symptom in hMPV positive children affected by ARTI (Table). In addition, our study showed that bronchiolitis was the most signiÞ cant clinical diagnosis associated with the presence of hMPV: 28% compared to 67% reported in other studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[2][3][4][5]8,12,13] According to other reports, [5] our results conÞ rmed that wheezing and cough were in order the most prevalent sign and symptom in hMPV positive children affected by ARTI (Table). In addition, our study showed that bronchiolitis was the most signiÞ cant clinical diagnosis associated with the presence of hMPV: 28% compared to 67% reported in other studies.…”
Section: Discussionsupporting
confidence: 84%
“…[1] Two distinct genotypes have been described called type A and B, with a variable prevalence in the world. [2][3][4][5][6] hMPV has been shown to be responsible for a signiÞ cant portion of ARTI in early infancy and childhood as well as in the elderly and immunocompromised host. [1,3,6,7] hMPV is the second virus after human respiratory syncytial virus (hRSV) with the highest prevalence of ARTI (43%) among children and infants.…”
mentioning
confidence: 99%
“…Respiratory samples were aliquoted and handled as reported previously (14,16). A panel of 17 respiratory viruses was investigated as reported previously (13), including HRVs (9) and human enteroviruses (HEVs) (21).…”
mentioning
confidence: 99%
“…The high rates of co-infection with hMPV-RSV reported in some studies may be due to the overlapping of virus seasons (Al-Sonboli et al 2006, Cuevas et al 2003, Principi et al 2006. No cases of hMPV-influenza A or other viruses analyzed were observed in this study, although co-infections of hMPV with other respiratory viruses had been reported in several studies (Heikkinen et al 2008, Sarasini et al 2006, Chano et al 2005, Manoha et al 2007, Sasaki et al 2005). …”
Section: Methodsmentioning
confidence: 45%